ANALISIS PEMBAGIAN HARTA WARISAN TERHADAP ANAK ANGKAT DALAM PERSPEKTIF HUKUM ISLAM - Andi Nurjayanti; Supardin; Muh. Jamal Jamil (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2022)
Abstract The subject of this research is the distribution of inheritance to adopted children from the perspective of Islamic law in Bontomanai Village, Rilau Ale District, Bulukumba Regency. This research is a qualitative research field study with an empirical juridical approach. The results of this study indicate that the distribution of inheritance to adopted children in Bontomanai Village, Rilau Ale District, Bulukumba Regency, that is, adoptive parents give property to their adopted children only to the extent of the heir's love because the distribution of inheritance has no measure and most parents adopt children from their own siblings and the settlement disputes through tudang sipulung or mapakiade. As for the distribution of inheritance to adopted children in the perspective of Islamic law, adopted children are not entitled to the inheritance of their adoptive parents because the adopted child is not an heir but if the adoptive parents want to share then article 209 in the KHI explains that the adopted child can get it through a mandatory will with condition is not more than 1/3 of the property. However, in the community of Bontomanai Village, the distribution of inheritance for adopted children is not in accordance with the rules set out in the KHI such as the absence of a dose and considering the adopted child as a biological child and giving inheritance is their responsibility. Keywords: Inheritance Law, Islamic Law, Adopted Children